Adequacy of Social Services for Persons with Disability of a Second Class City in Negros Occidental - Marcella, Cherry Belle R.; Nalumen, Ma. Dolores J. (Philippine Social Science Journal, 2020)
Persons with Disability (PWDs) comprise one billion or fifteen percent (15%) of the world’s total population. Adequacy of social services plays a vital role in realizing the rights and welfare of the PWDs. This includes providing them with an adequate standard of living and a basic level of income security that will help reduce their levels of poverty and vulnerability. The Department of Social Welfare and Development (DSWD) is the primary government agency mandated to develop and coordinate social protection and poverty reduction solutions for and with the poor, vulnerable, and disadvantaged. Hence, this study explored how adequate are the social services under the five elements: health, education, livelihood, social aspect, and empowerment provided by the CSWD Office of a second-class city in Negros Occidental. It also explored the challenges faced by the respondents in availing of the social services and their recommendations to overcome those challenges.